HS1, 2 Ig Enhancer Alleles Association to AIDS Progression in a Pediatric Cohort Infected with a Monophyletic HIV-Strain. (20th May 2014) - Montesano, Carla; Giambra, Vincenzo; Frezza, Domenico; Palma, Paolo; Serone, Eliseo; Gattinara, Guido Castelli; Mattei, Maurizio; Mancino, Giorgio; Colizzi, Vittorio; Amicosante, Massimo
Abstract : Alteration in the humoral immune response has been observed during HIV infection. The polymorphisms of enhancer HS1, 2, member of the 3′ regulatory region of the Ig heavy chain cluster, may play a role in the variation of the humoral response leading to pathological conditions. To assess the role of the HS1, 2 polymorphic variants in the progression of AIDS, the HS1, 2-A allelic frequencies were investigated in a cohort of HIV infected pediatric subjects from a nosocomial outbreak with a monophyletic strain of HIV. From a total group of 418 HIV infected children in the outbreak cohort, 42 nonprogressors and 31 progressors without bias due to antiretroviral therapy were evaluated. HS1, 2 allele *1 has been associated with nonprogressors (allelic frequency: 51.19% versus 33.87% in progressors, OR 0.5, and P = 0.0437 ), while allele *2 has been associated with progression (allelic frequency: 48.39% versus 30.95% in nonprogressors, OR 2.1, and P = 0.0393 ) . Further, only subjects carrying allele *2 in absence of allele *1, either in homozygous condition for allele *2 [nonprogressors 2/42 (4.76%), Progressors 7/31 (22.58%), OR 5.8, and P = 0.0315 ] or in combination with other allelic variants [nonprogressors 7/42 (16.67%), Progressors 13/31 (41.93%), OR 3.61, and P = 0.0321 ], have been associated with HIV progression to AIDS. In conclusion, while the HS1, 2 allele *1 has a protective effect on HIV progression when present, allele *2 is associated with progression toward AIDS when allele *1 is absent.